A inserção dos terapeutas ocupacionais na rede de atenção à saúde do Sistema Único de Saúde no Rio Grande do Sul - Siqueira, Gabriela Nunes (2022)
The occupational therapist is the professional who holds expertise in the fields of health, education, culture, and social assistance. Research on the involvement of this professional in health actions and services is essential to understand their participation in the Sistema Único de Saúde (SUS). This study aims to identify the insertion of these professionals in the health care network of the SUS, in the health macro-regions of the state of Rio Grande do Sul, between the years 2015 and 2020. For this, a cross-sectional and descriptive research was carried out, with data obtained from the database of the Departmento de Informatica do SUS (DATASUS), about the vacancies filled by professionals working in the SUS. It was possible to analyze the region of each Coordenadoria Regional de Saúde (CRS) of the state, verify the establishments that are affiliated to the SUS, and examine the characteristics of the vacancies. It was verified that the 2nd CRS has the largest number of vacancies, and the 18th CRS has the highest rate of vacancies, 8.8 per 1000 inhabitants. The establishments that offer vacancies, in the majority, were maintained (54.0%) of municipal management (74.7%), without teaching activity (76.5%) and with spontaneous and referenced demand (62.8%). As for the professionals who filled the vacancies, they predominantly worked 3 shifts (66.1%), under contract (74.1%), were not self-employed (86.7%), were legal entity (98.8%) and SUS professionals (89.2%). An increase in the offer of vacancies was observed during the study period, reaching the highest number (700) in 2020. In this study, it was possible to identify the growth of the profession, presenting, on a larger scale, in services that are located in the capital, in the beach region or close to the training centers of these professionals. The results of this research collaborate with the qualification of information about the occupational therapist in the state and provides information subsidies that can guide the implementation of public policies for the insertion and training of the occupational therapist for work in Rio Grande do Sul.